Long term association between of maternal preconception hemoglobin and anemia and child health and development in Vietnam - Young, Melissa F.; Nguyen, Phuong Hong; Tran, Lan Mai; Khuong, Long Quynh; Martorell, Reynaldo; Ramakrishnan, Usha (Elsevier, 2023)
Background: The long-term association between preconception maternal hemoglobin (Hb) concentrations and child health and development is unclear. Objective: We examined associations between maternal preconception Hb concentrations and anemia with: a) birth outcomes (weight, length, preterm, gestational age, small-for-gestational-age); b) child Hb at 3 mo, 6 mo, 12 mo, and 24 mo; c) motor and mental development at 12 mo and 24 mo (Bayley scales for infant development) and cognitive functioning at 6-7y (Wechsler Intelligence Scale for Children). Methods: We used data from a randomized controlled trial (PRECONCEPT) conducted in Vietnam. Over 5000 women who were intending to conceive were recruited and offspring were prospectively followed from birth (n=1599) through 6-7y (n=1318). Multivariable linear and logistic regressions were used to assess the association between preconception Hb or anemia (Hb < 11g/dL) on child health and development outcomes, adjusted by supplementation group (tested for interactions) and confounding at maternal, child and household levels. Results: At preconception enrollment, 20% of the women were anemic. Maternal preconception Hb was positively associated with child Hb at 3 mo (0.06; 95% CI: 0.01,0.12), 6 mo (0.08; 95% CI: 0.03,0.13), 12 mo (0.10; 95% CI: 0.04-0.15) and 24 mo (0.07; 95% CI: 0.02,0.12). Likewise, maternal preconception Hb was associated with reduced risk of child anemia at 6mo (0.89; 95% CI: 0.81-0.98), 12 mo (0.81; 95% CI: 0.74-0.89) and 24 mo (0.87; 95% CI: 0.79-0.95). Maternal preconception anemia was negatively associated with cognition (-1.64; 95% CI: -3.09, -0.19) and language development (-1.61; 95% CI: -3.20, -0.03) at 24mo. Preconception Hb was not associated with birth outcomes or cognitive outcomes at 6-7y. Conclusion: Maternal preconception Hb was associated with child Hb across the first 1000 days of life. However, preconception Hb was not a significant predictor of birth outcomes or cognitive outcomes at 6-7y in this cohort from Vietnam.